Community assistance on making TESIPDATI tea as an alternative to reduce high blood pressure in Jayapura county - Novianti, Novianti P.E Mambrasar; Debora, Debora P.R Panjaitan; Natalia, Natalia Mendila; Brenda, Brenda S Ayomi; Rohmani, Rohmani; Blestina, Blestina Maryorita (Department of Nursing, Faculty of Health Sciences, Universitas Brawijaya., 2024)
Backgraound : One of the most dangerous non-communicable cardiovascular diseases in the world is hypertension. The World Health Organization states that sustained high blood pressure is characterized by systolic values above 140 mmHg or diastolic values above 90 mmHg. Hypertension, often asymptomatic, can damage vital organs such as the heart, brain, and kidneys, earning it the nickname